Sociologia e consubstancialidade de gênero em tempos de fundamentalismo religioso, conservadorismo e reformas educacionais neoliberais - Botter, Elaine Regina Okado [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
A pesquisa tem como objetivo principal analisar as influências dos movimentos conservadores, liberais e fundamentalistas religiosos no que tange a educação de gênero do Brasil, especificamente no Ensino de Sociologia. Para atingir o objetivo principal propomos refeletir sobre os movimentos de direita, especialmente a Escola Sem Partido e o que denominam “ideologia de gênero”, além de vincular a sua relação com as reformas educacionais. Relevante examinar gênero cientificamente à fim de desmistificar impressões do senso comum. Por fim, o trabalho busca avalliar os limites dos materiais didáticos oferecidos pelo SPFE na disciplina de sociologia usando como aporte teórico as contribuições acerca da consubstancialidade de gênero. Foram analisados o material da 1ª e 2 ª série quarto bimestre e 3ª série segundo bimestre. Isto porque, esses bimestres apresentam os raros e rasos momentos em que o docente de sociologia consegue abordar o tema gênero.

The main objective of the research is to analyze the influences of conservative, liberal and fundamentalist religious movements with regard to gender education in Brazil, specifically in the teaching of sociology. In order to achieve the main objective, we propose to reflect on the right-wing movements, especially the Escola Sem Partido and what they call “gender ideology”, in addition to linking their relationship with educational reforms. It is relevant to scientifically examine gender in order to demystify common sense impressions. Finally, this research seeks to evaluate the limits of the didactic materials offered by SPFE in the discipline of sociology using theoretical contributions about the consubstantiality of gender. The material from the 1st and 2nd years was separated from the fourth bimester and 3rd year from the second bimester. This is because these bimonths present the rare and shallow moments, in which the sociology professor manages to approach the theme of gender.
Sociology and gender consubstantiality in times of religious fundamentalism, conservatism and neoliberal educational reforms
Keywords: Ensino de sociologia; Gênero; Escola Sem Partido; Reformas educacionais; Material SPFS; Teaching of sociology; Genre; School Without Party; Educational reforms; SPFE material